Branching space-times theory and applications - Belnap, Nuel D. 1930-2024; Müller, Thomas 1969-; Placek, Tomasz 1960- (Oxford University Press, 2021)
This monograph presents a detailed exposition of the formal theory of Branching Space-Times (BST). The theory presented here by Nuel Belnap, Thomas Mèuller, and Tomasz Placek describes how real possibilities can be anchored in a spatio-temporal world that is rudimentarily relativistic.
Also issued in print: 2021. - "This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Home page. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on November 15, 2021)
Keywords: Space and time